THE CONSTITUTIONALISATION OF LABOUR LAW: NO PLACE FOR A SUPERIOR LABOUR APPEAL COURT IN LABOUR MATTERS (PART 1): BACKGROUND TO SOUTH AFRICAN LABOUR COURTS AND THE CONSTITUTION - Stefan van Eck (Obiter, 2022)
This article explores the status of the Labour Appeal Court under South Africa's constitutional democracy. The stages of development of this country's labour laws have coincided with the establishment of new sets of labour dispute resolution fora: firstly, the Industrial Court; secondly, the labour courts under our present constitutional democracy; and thirdly, a yet to be implemented new dispute resolution paradigm under the proposed Superior Courts Bill. The focus of this contribution is on the influence of the provisions of the Constitution on these developments, and the gradual erosion of the exclusive appellate powers of the Labour Appeal Court by the Supreme Court of Appeal, and the Constitutional Court, in the assertion of their power to serve as highest courts in all labour matters.